2014
DOI: 10.3906/vet-1308-38
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crossing Polish and foreign pig breeds on physicochemical traits of longissimus lumborum muscle

Abstract: In this study, free vibrations of thick composite cylindrical and spherical shell panels with uniformly distributed attached masses were analyzed, using the standard Galerkin procedure. The stiffness effect of the distributed attached mass was taken into account for the first time, and the results were compared with well-known published results for which this effect was not considered. Various results for effects such as thickness, radii of curvature, and elasticity moduli are presented in this paper. Mass ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The medium level of muscle glycolysis allows the pH of Tibetan pigs to average between that of YP and QYP, while the relatively high levels of tricarboxylic acid cycle-related genes are expressed. Meat color is an important sensory indicator for the evaluation of pork [39,40]. Pork from TP and QYP have higher a* and lower b* values, which implies that Chinese pork sales are based on cultural and visual perceptions of meat freshness.…”
Section: Carcass Traits and Meat Quality Differences Between Yorkshirmentioning
confidence: 99%
“…The medium level of muscle glycolysis allows the pH of Tibetan pigs to average between that of YP and QYP, while the relatively high levels of tricarboxylic acid cycle-related genes are expressed. Meat color is an important sensory indicator for the evaluation of pork [39,40]. Pork from TP and QYP have higher a* and lower b* values, which implies that Chinese pork sales are based on cultural and visual perceptions of meat freshness.…”
Section: Carcass Traits and Meat Quality Differences Between Yorkshirmentioning
confidence: 99%
“…Color Warriss and Brown (1995) showed that the value of L* within the range of 49-60 for the longissimus dorsi muscle is perceived as desirable by consumers. An excessively pale meat color is undesirable consumers and also indicates the PSE meat defect (Warriss and Brown, 1995;Joo et al, 1999;Gajewczyk et al, 2014). Polish native breeds color is darkerfrom 43.88 to 54.94 (Table 4), than that observed in Polish Landrace -56.52 by Kasprzyk et al (2015), and53.07-54.26 (Wojtysiak andKaczor, 2011).…”
Section: Initial Ph Values Given In Tablementioning
confidence: 87%